The Influence of Marketing Mix towards Consumer Purchase Intention: The Case of Bank Aceh Syariah - Muhammad Iqbal Fajri; Jerry Heikal (Emerging Markets : Business and Management Studies Journal, 2022)
This article examines the influence of Marketing Mix (4Ps) on consumer buying decisions on Islamic banking products, savings, and mortgages. This research method is quantitative. This research population of Bank Aceh Syariah customers using Smart-PLS and surveyed with a Likert scale. The results showed that Price and Place have a highly positive impact on consumer decisions. In contrast, the promotion positively impacts consumer decisions on the sharia mortgage account at Bank Aceh Syariah.